Roh Kudus: Pribadi Ketiga dari Allah Trinitas─ Api Penginjilan Bagi Bangsa-bangsa - Kamadjaja, Djumailah; Sulistiyo, Ferdiand; Grace Wong, Fingfing Keren (Sekolah Tinggi Teologi Aletheia, 2024)
Abstract:The doctrine of the Trinity states that God is Father, Son, and Holy Spirit, three persons in one essence. The Holy Spirit is the third person of the Trinity, and as a divine person, the Holy Spirit has personality, will, and feelings. The typology of the Holy Spirit as ‘fire’ is closely related to evangelism because the Holy Spirit gives power and courage to Christ’s disciples to preach the Gospel of the Kingdom of God. However, there are still differences in understanding of the work of the Holy Spirit in contemporary evangelism, which can cause its effectiveness to decrease. To overcome this problem, the author uses library research methods to obtain data about the Holy Spirit and the Fire of Evangelism. Through the data analysis process, it was discovered that the work of the Holy Spirit is a driving force for evangelism by empowering God’s people so that the Gospel spreads to the ends of the earth. The work of the Holy Spirit in evangelisation is essential for the Church to fulfil its mission of bearing witness to Christ and making disciples of all nations for Christ. The role of the Holy Spirit as the Fire of Evangelism is very important because it highlights the transformative power of the Holy Spirit in the lives of believers. The Holy Spirit empowers believers to live out their faith and bear witness to Christ, even in the face of persecution and opposition. The Holy Spirit is the primary agent of evangelism, guiding and directing the Church in world evangelisation. Abstrak: Doktrin Trinitas menyatakan bahwa Allah adalah Bapa, Putra, dan Roh Kudus, tiga pribadi dalam satu hakikat. Roh Kudus adalah pribadi ketiga dari Trinitas, dan sebagai pribadi ilahi, Roh Kudus memiliki kepribadian, kehendak, dan perasaan. Tipologi Roh Kudus sebagai 'api' erat kaitannya dengan penginjilan, karena Roh Kudus memberikan kuasa dan keberanian kepada murid-murid Kristus untuk memberitakan Injil Kerajaan Allah. Namun demikian, masih terdapat perbedaan pemahaman tentang pekerjaan Roh Kudus dalam penginjilan masa kini yang dapat menyebabkan efektivitasnya menurun. Untuk mengatasi permasalahan tersebut, penulis menggunakan metode penelitian kepustakaan untuk memperoleh data tentang Roh Kudus dan Api Penginjilan. Melalui proses analisis data ditemukan bahwa pekerjaan Roh Kudus menjadi penggerak penginjilan dengan memberdayakan umat Tuhan sehingga Injil tersebar sampai ke ujung bumi. Pekerjaan Roh Kudus dalam penginjilan sangat penting bagi Gereja untuk memenuhi misinya memberikan kesaksian tentang Kristus dan menjadikan semua bangsa murid Kristus. Peran Roh Kudus sebagai Api Penginjilan sangat penting karena menyoroti kuasa transformatif Roh Kudus dalam kehidupan orang-orang percaya. Roh Kudus memberdayakan orang-orang percaya untuk menghidupi iman mereka dan memberikan kesaksian tentang Kristus, bahkan ketika menghadapi penganiayaan dan perlawanan. Roh Kudus adalah agen utama penginjilan, membimbing dan mengarahkan Gereja dalam penginjilan sedunia.